A partial revision of the genus Notomastus (Polychaeta: Capitellidae) with a description of a new species from the Gulf of Mexico - Ewing, R. Michael (Proceedings of the Biological Society of Washington, 1982)
An emended diagnosis for the genus Notomastus (Polychaeta: Capitellidae) is proposed with two closely related genera, Rashgua Wesenberg-Lund and Paraleiocapitella Thomassin, considered as junior synonyms. A new species of Notomastus from the Gulf of Mexico, N. daueri, is described.
World Polychaeta Database (WPolyDb)